Review of a frugal cooling mattress to induce therapeutic hypothermia for treatment of hypoxic-ischaemic encephalopathy in the UK NHS - Giulia Dallera; Mark Skopec; Cheryl Battersby; James Barlow; Matthew Harris (Globalization and Health, 2022)
Abstract Hypoxic ischaemic encephalopathy (HIE) is a major cause of neonatal mortality and disability in the United Kingdom (UK) and has significant human and financial costs. Therapeutic hypothermia (TH), which consists of cooling down the newborn’s body temperature, is the current standard of treatment for moderate or severe cases of HIE. Timely initiation of treatment is critical to reduce risk of mortality and disability associated with HIE. Very expensive servo-controlled devices are currently used in high-income settings to induce TH, whereas low-income settings rely on the use of low-tech devices such as water bottles, ice packs or fans. Cooling mattresses made with phase change materials (PCMs) were recently developed as a safe, efficient, and affordable alternative to induce TH in low-income settings. This frugal innovation has the potential to become a reverse innovation for the National Health Service (NHS) by providing a simple, efficient, and cost-saving solution to initiate TH in geographically remote areas of the UK where cooling equipment might not be readily available, ensuring timely initiation of treatment while waiting for neonatal transport to the nearest cooling centre. The adoption of PCM cooling mattresses by the NHS may reduce geographical disparity in the availability of treatment for HIE in the UK, and it could benefit from improvements in coordination across all levels of neonatal care given challenges currently experienced by the NHS in terms of constraints on funding and shortage of staff. Trials evaluating the effectiveness and safety of PCM cooling mattresses in the NHS context are needed in support of the adoption of this frugal innovation. These findings may be relevant to other high-income settings that experience challenges with the provision of TH in geographically remote areas. The use of promising frugal innovations such as PCM cooling mattresses in high-income settings may also contribute to challenge the dominant narrative that often favours innovation from North America and Western Europe, and consequently fight bias against research and development from low-income settings, promoting a more equitable global innovation landscape.